Counting Condensation Nuclei in the Antarctic Ozone Mission - Wilson, James Charles (1994)
The work done on this grant primarily concerns the measurement of aerosol in the stratosphere from NASA ER-2 aircraft in studies of stratospheric ozone depletion in the northern and southern hemispheres. The ER-2 Condensation Nucleus Counter (CNC) measures the number concentration of particles in the diameter range of approximately 0.01 to 1 micron. The Passive Cavity Aerosol Spectrometer measures size distributions in the 0.17 to 3 micron diameter range. This instrument was upgraded during this grant period to a Focused Cavity Aerosol Spectrometer (FCAS). This upgrade permitted the instrument to measure particles as small as 0.05 micron in diameter. The inlet for the PCAS and FCAS was modified and characterized under this grant so that the modifications to the aerosol due to anisokinetic sampling and heating upon sampling and in transport to the measurement location were accounted for in the data analysis. These measurements permitted observations of particle production in the southern hemisphere winter polar vortex and observation of the impact of denitrification on the number concentration of the aerosol in the denitrified air. In the northern polar vortex, the measurements provided a characterization of the sulfate aerosol. Following the eruption of Mount Pinatubo in 1991, the measurements permitted an accurate characterization of the sulfate aerosol enhancements resulting from the eruption. This led to studies of the impact of heterogeneous chemistry on the partitioning of the partitioning of the reactive nitrogen species and the partitioning of the chlorine reservoir.